Gas turbine efficiency and ramp rate improvement through compressed air injection. (June 2021) - Abudu, Kamal; Igie, Uyioghosa; Minervino, Orlando; Hamilton, Richard
With the transition to more use of renewable forms of energy in Europe, grid instability that is linked to the intermittency in power generation is a concern, and thus, the fast response of on-demand power systems like gas turbines has become more important. This study focuses on the injection of compressed air to facilitate the improvement in the ramp-up rate of a heavy-duty gas turbine. The steady-state analysis of compressed airflow injection at part-load and full load indicates power augmentation of up to 25%, without infringing on the surge margin. The surge margin is also seen to be more limiting at part-load with maximum closing of the variable inlet guide vane than at high load with a maximum opening. Nevertheless, the percentage increase in the thermal efficiency of the former is slightly greater for the same amount of airflow injection. Part-load operations above 75% of power show higher thermal efficiencies with airflow injection when compared with other load variation approaches. The quasi-dynamic simulations performed using constant mass flow method show that the heavy-duty gas turbine ramp-up rate can be improved by 10% on average, for every 2% of compressor outlet airflow injected during ramp-up irrespective of the starting load. It also shows that the limitation of the ramp-up rate improvement is dominated by the rear stages and at lower variable inlet guide vane openings. The turbine entry temperature is found to be another restrictive factor at a high injection rate of up to 10%. However, the 2% injection rate is shown to be the safest, also offering considerable performance enhancements. It was also found that the ramp-up rate with air injection from the minimum environmental load to full load amounted to lower total fuel consumption than the design case.